Identification of Priority Areas for Increased Testing Using Geospatial Mapping of Incident HIV Cases Near Charleston, South Carolina. (August 2019) - Gedney, Ryan; Butler Willis, Kimberly; O'Brien, Aaron; Luciano, Michael; Richardson, Katherine J; Meissner, Eric G
Analysis of disease incidence using geospatial mapping techniques can enhance targeted public health efforts in resource-limited settings. While data for HIV incidence are readily available for some metropolitan regions, there is no existing resource that maps HIV incidence geospatially for Charleston, South Carolina and surrounding counties. To facilitate the public health approach to address the HIV epidemic in this region, we used data collected by the South Carolina Department of Health and Environmental Control (SC-DHEC) from 2014 to 2015 to generate local geospatial maps of disease incidence and identify specific areas that may benefit from increased testing and educational efforts. We identified specific zip codes in which there were a high number of cases from patients residing in those areas, but a low number of providers reporting new cases, and we describe ongoing efforts to address this disparity. This analysis identifies a local, collaborative approach to address the HIV epidemic using routinely collected surveillance data.